2002
DOI: 10.1063/1.1521580
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation and Raman spectroscopy studies of boron carbide single crystals

Abstract: The measurements of hardness and elastic modulus have been conducted on the (0001) and (101̄1) faces of B4.3C single crystals using nanoindentation. The results are in good agreement with the corresponding values obtained using a conventional microhardness technique on polycrystalline ceramics. Raman microspectroscopy analysis of the nanoindentations shows the appearance of several bands which suggest dramatic structural changes in the indented material. Localized contact loading may lead to damage in boron ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
134
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(143 citation statements)
references
References 15 publications
8
134
0
1
Order By: Relevance
“…The H and E values of n-B 4 C are comparable to those of microcrystalline B 4 C at similar loads [17][18][19][20] , but less than those of single-crystal B 4 C (ref. 21). The reduced hardness and elastic modulus can be attributed to the presence of nanoporosity and soft amorphous carbon at GBs in n-B 4 C. The fracture toughness of n-B 4 C was measured by nanoindentation according to the following equation 22 :…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The H and E values of n-B 4 C are comparable to those of microcrystalline B 4 C at similar loads [17][18][19][20] , but less than those of single-crystal B 4 C (ref. 21). The reduced hardness and elastic modulus can be attributed to the presence of nanoporosity and soft amorphous carbon at GBs in n-B 4 C. The fracture toughness of n-B 4 C was measured by nanoindentation according to the following equation 22 :…”
Section: Resultsmentioning
confidence: 99%
“…At low loading levels, the Raman bands extending from 350 to 1,200 cm − 1 are in good agreement with the unindented spectra, and the characteristic Raman bands are located at 481, 531, 732, 830, 1,004 and 1,086 cm − 1 . At the loading levels above 600 mN, intense Raman bands at 1,325 and 1,360 cm − 1 , followed with short peaks at 1,530 and 1,590 cm − 1 and 1,810 cm − 1 , can be observed 21,26 , indicating partial phase transition from crystalline to amorphous boron carbide (a-B 4 C) along with the presence of amorphous carbon.…”
Section: Mechanical Properties and Raman Spectroscopy Analysismentioning
confidence: 99%
“…So far, most of experimental results show that boron carbides undergo a transition to amorphous phase at far lower pressure than the above. Gogotsi's group reports a phase transition of boron carbide to disordered or undefined phases by static indentation technique, and the estimated pressure is about 44-49 GPa [129,130]. Also, in their paper they cite a transition pressure of about 20 GPa measured by Manghnani.…”
Section: Gap Problemmentioning
confidence: 95%
“…Chen et al reported the observation of shock-induced local amorphization bands that might be responsible for the low fracture toughness of B 4 C [6]. In addition, amorphization bands had been observed in nanoindentation and scratch experiments, where the loading rate is much lower than for dynamical shock loading [16][17][18][19]. Particularly, recent nanoindentation experiments revealed amorphous shear bands along the (0111) plane [19].…”
mentioning
confidence: 99%